Long QT Syndrome Course Associated with New Coronavirus Infection. Clinical Case - Sabina Kh. Israfilova; Tatiana K. Kruchina; Marina V. Zhdanova; Lada О. Klimenko; Novik A. Gennadiy (Вопросы современной педиатрии, 2025)
Background. Long QT syndrome is hereditary disease, cardiac canalopathy variant, characterized by syncope and high risk of sudden cardiac death due to occurrence of polymorphic ventricular tachycardia (VT), torsade de pointes, and ventricular fibrillation. Acute respiratory viral infection may aggravate clinical course of primary electrical heart diseases. Clinical case description. 14-year-old female patient was transferred to infectious diseases hospital from another hospital with positive PCR test on new coronavirus infection (COVID-19) after loss of consciousness in November 2021. Syncope was first noted at the age of 12, however then did not recur, and their examination and treatment were postponed due to the COVID-19 pandemic. Syncopal states continued during COVID-19. Cardiac examination was performed at infectious diseases hospital: recurrent VT, torsade de pointes, was diagnosed along with QT interval prolongation. The girl's condition has improved after the treatment and selection of antiarrhythmic therapy. 15 days later negative PCR test for SARS-CoV-2 was received, and the patient was transferred to specialized hospital, where the long QT syndrome was confirmed, and dual-chamber cardioverter defibrillator was installed. Conclusion. This clinical case demonstrates that ARVI can aggravate the course of existing primary arrhythmia and emphasizes the crucial role of timely diagnosis and integrated approach to the management of patients with genetically determined cardiac arrhythmias.